2016
DOI: 10.1038/ng.3623
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 15 genetic loci associated with risk of major depression in individuals of European descent

Abstract: Despite strong evidence supporting the heritability of Major Depressive Disorder, previous genome-wide studies were unable to identify risk loci among individuals of European descent. We used self-reported data from 75,607 individuals reporting clinical diagnosis of depression and 231,747 reporting no history of depression through 23andMe, and meta-analyzed these results with published MDD GWAS results. We identified five independent variants from four regions associated with self-report of clinical diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
735
10
8

Year Published

2017
2017
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 716 publications
(795 citation statements)
references
References 37 publications
20
735
10
8
Order By: Relevance
“…A second possible explanation is that SSRIs treatment response likely represents a complex, highly polygenic trait, influenced by a large number of genes with small effects and interacting environmental factors. Increasing the sample size for the current pharmacogenomics studies seems to be the only available option to be successful in this process, as previously been observed in MDD GWAS [59]. Genetic variants associated with MDD were undetectable for smaller sample sizes (< 200,000) [59].…”
Section: Maoamentioning
confidence: 80%
See 2 more Smart Citations
“…A second possible explanation is that SSRIs treatment response likely represents a complex, highly polygenic trait, influenced by a large number of genes with small effects and interacting environmental factors. Increasing the sample size for the current pharmacogenomics studies seems to be the only available option to be successful in this process, as previously been observed in MDD GWAS [59]. Genetic variants associated with MDD were undetectable for smaller sample sizes (< 200,000) [59].…”
Section: Maoamentioning
confidence: 80%
“…To date, GWAS approaches have identified 18 loci contributing to the risk of MDD [20,24,59] and over 8 loci associated with BPD [55,63,84,92,106], including shared genetic loci located in the CACNA1C, CACNB2, AS3MT, ITIH3, and CCDC68 genes [22]. An extension of the GWAS approaches such as polygenic score analysis [87], bivariate restricted maximum likelihood (REML) in genome-wide complex trait analysis (GCTA) [21] and linkage disequilibrium (LD) score regression have strongly suggested that mood disorders are polygenic in nature, in that multiple genetic variants interacting with environmental factors contribute to the development of the diseases [87].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigators of an ongoing large-scale GWAS of major depressive disorder (N = 368,890) in the 23andMe cohort shared association results for the loci identified in our DS and neuroticism analyses (Online Methods and Supplementary Table 15) 21 . Because the depression sample overlaps with our SWB sample, we did not request a lookup of the SWB-associated SNPs.…”
Section: Lookup Of Ds and Neuroticism Lead-snpsmentioning
confidence: 99%
“…We did not request results for the SNPs identified in the SWB or proxy-phenotype analyses, since these were both conducted in samples that overlap with 23andMe's depression sample. For details on association models, quality-control filters, and the ascertainment of depression status, we refer to the companion study 21 . The p-values we report are based on standard errors that have been inflated by the square by the intercept from an LD score regression 10 .…”
Section: Bayesian Credibility Analysesmentioning
confidence: 99%